OH & S Management Systems a practical approach - Nicholas and Smith Pty.Ltd. ([Australia] : Nicholas & Smith)
This video and guide uses the experience of two Australian case studies to show that OH&S management systems can be successfully implemented and achieve tangible changes in the work environment
Title from title screen
Keywords: Management; Management information systems